All-fiberized, femtosecond laser at 1912 nm using a bulk-like MoSe2 saturable absorber - Lee, Jinho; Koo, Joonhoi; Lee, Junsu; Jhon, Young Min; Lee, Ju Han (OPTICAL SOC AMER, 2017)
An all-fiberized, mode-locked fiber laser that operates in the 1912 nm region with a saturable absorber (SA) that is based on a composite consisting of bulk-like, molybdenum diselenide (MoSe2) particles and polyvinyl alcohol (PVA), is experimentally demonstrated here. The MoSe2 particles were prepared using liquid phase exfoliation (LPE) without a centrifugation. The SA was implemented on a side-polished fiber platform and deposited with the MoSe2/PVA. The saturation power and modulation depth of the SA were measured as similar to 25.7 W and similar to 4.4%, respectively. Using the prepared SA, the stable soliton pulses with a temporal width of similar to 920 fs could be produced at 1912 nm from a thulium-holmium (Tm-Ho) co-doped fiber ring cavity. The mode-locked pulses were operated at a repetition rate of similar to 18.21 MHz, and a 3-dB bandwidth was measured as similar to 4.62 nm. The signal-to-noise ratio (SNR) was measured as similar to 65 dB at the fundamental frequency of similar to 18.21 MHz. To the best of the authors' knowledge this is the first time demonstration of the use of a saturable absorber based on a transition metal dichalcogenide for femtosecond mode-locking of a 2-mu m fiber laser. (C) 2017 Optical Society of America
Keywords: TRANSITION-METAL DICHALCOGENIDES; EVANESCENT FIELD INTERACTION; MOLYBDENUM DISELENIDE MOSE2; CHEMICAL-VAPOR-DEPOSITION; BLACK PHOSPHORUS; PULSE GENERATION; OPTICAL-ABSORPTION; MODE-LOCKING; ENERGY QUANTIZATION; GRAPHENE